Spinal accessory neurotization for restoration of elbow flexion in avulsion injuries of the brachial plexus - P. Songcharoen (2018)
Traumatic root avulsion brachial plexus injuries in 216 patients were treated with spinal accessory-musculocutaneous neurotization to restore elbow flexion. The average postoperative follow-up period was 6 years, with a minimum of 2 years for all patients. The percentage of satisfactory biceps recovery (MRC III or better) was 72.5%. The average interval between the operation and MRC III motor recovery was 17 months. The percentage of poor results increased from 25.5% to 62.5% in patients who underwent operation later than 9 months after injury. This method of neurotization produces a result comparable with, if not better than, the results of other types of neurotization in restoration of elbow flexion.